Control system of the autonomous underwater helicopter for pipeline inspection. (15th December 2022) - Hu, Sijie; Feng, Rendong; Wang, Zhanglin; Zhu, Chengcheng; Wang, Zhikun; Chen, Ying; Huang, Haocai
Abstract: For decades, in order to fully transport energy and rationally redistribute resources, humans have laid a large number of underwater pipelines in rivers, lakes and oceans to transport resources. However, due to corrosion, load, natural vibration, and crustal movement, underwater pipelines will undergo fatigue fracture, causing resource leakage, environmental pollution and economic losses. In recent years, the problem of maintenance of underwater pipelines has become one of the most difficult problems that need to be solved. And the internal inspection of the pipeline is the key problem. In this paper, we successfully realize this through algorithm and experiments. Here we show a circular dish-shaped underwater helicopter (AUH) that used to realize the depth-fixed line tracking control in the underwater pipeline. This work proposed a priority control system which combines depth control and line tracking control well and an underwater image processing algorithm flow to identify the line well. Highlights: A control system that realize the depth control and line tracking control in underwater pipeline. A control method applied on a circular dish-shaped underwater helicopter (AUH). An underwater image processing algorithm to identify the line well in underwater pipeline.